The bells of Santa Maria in Monserrato degli Spagnoli - Rodriguez Suarez, Alex (Anthologica Annua, 2024)
The history and the art of the Spanish national church in Rome, known as the church of Santiago, San Ildefonso and Santa Maria di Monserrato degli Spagnoli, has been the object of research. Nevertheless, its bells have not received any scholarly interest so far. This short contribution deals with these artefacts, four bells dated to the fifteenth, eighteenth and twentieth centuries. Their inscriptions and artistic features are described and placed in the evolution of bell casting in Rome. Moreover, two documents related to one of the bells (no. 2), the contract between the church and the bell founder and the receipt, are discussed. They provide details about the production of the bell in 1746.